Digital Parenting dan Peran Orang Tua dalam Mengelola Paparan Media Digital pada Anak Usia Dini: Systematic Literature Review - Wedya Puspita; Karunia Muda Setya Utama; Dewi Masitoh; Mistia Ningsih (Journal of Educational Science and E-Learning, 2026)
The rapid growth of digital technology has reshaped early childhood parenting, as young children now grow up alongside gadgets, television, and online applications from a very early age. This condition challenges parents in managing the duration, type, and context of children's digital media exposure so that it continues to support healthy development. This study aims to systematically examine the role of parents in managing digital media exposure among young children and its impact on child development. This study used a Systematic Literature Review (SLR) method following the PRISMA stages, searching articles in the Google Scholar, ScienceDirect, and Springer Link databases published between 2021 and 2025. After a screening process based on inclusion and exclusion criteria, 15 articles were deemed eligible for analysis. The findings show that common digital parenting strategies include restrictive mediation, instructive mediation, and co-viewing/co-use, whose effectiveness is influenced by parental digital literacy, parenting style, and parental awareness. Unmanaged digital media exposure is associated with sleep disturbances, language delay, emotional-regulation problems, and reduced social interaction in children. This study recommends strengthening parental digital literacy and early media-use accompaniment as preventive measures.